PENERAPAN METODE STABLE TAIL ADJUSTED RETURN RATIO (STARR) DALAM PENGUKURAN KINERJA INVESTASI: Kasus Data Berdistribusi T-Student - Anjaningrum, Widiya Dewi (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
The purpose of this study was to determine the appropriate approach and method for measuring the performance of the investment, if the return data provided just a little or the data don’t follow the normal distribution. Then, apply it in a real case, that is, investment portfolio performance measurement of a pension fund managed by a private university in Malang town. Data processing was aided by MS Excel which the steps are calculating the average return (mean), standard deviation, VaR and CVaR, deviation VaR and CVaR, BI rate and STARR both in the case of a Gaussian distribution and T-Student. The result of the analysis showed that the T-Student distribution approach and STARR method are better to use for measuring pension fund investment performance than the Gaussian distribution approach and traditional Sharpe method. Two investment instruments that have the best performance are a Direct Placement and Property.